Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the impact of environment and climate change on Vietnam's economic growth. Vietnam's economy and population are expected to be increasingly affected by climate change. In addition, the country's growth model-which permitted quick reduction of poverty-has been unsustainably relying on mining and natural resources. The level of air, land and water pollution has also increased in the country. Well aware of the critical challenges faced by the country, the government has undertaken numerous initiatives and programs to adapt the economy to climate change risks and transform the growth model to support an environmental-friendly economy, but significant challenges remain.